Regenerative endodontics: Changes, chances, and challenges of revascularization in pediatric dentistry - Mamta Dali; Laleet Rajbanshi (Wolters Kluwer Medknow Publications, 2014)
Pulp vitality is extremely important for the tooth viability, since it provides nutrition and acts as biosensor to detect pathogenic stimuli. Treatment of the young permanent tooth with a necrotic root canal system and an incompletely developed root is very difficult. Few acceptable results have been achieved through apexification, but use of long-term calcium hydroxide might alter the mechanical properties of dentin. Regenerative endodontic procedures aim at the regeneration of pulp and dentin of the injured teeth. The present article reviews the recent approach of pulp revascularization and provides an overview of its methods with possible future potential of regenerating pulp as a routine dental procedure in pediatric dentistry.